Recent advances in intranasal delivery of therapeutic peptides - Kharuk, Sviatoslav; Shturmak, Andrii; Shvadchak, Volodymyr (Journal of Vasyl Stefanyk Precarpathian National University. Biology, 2024)
Treatment of neurodegenerative disorders requires delivery of drugs into the central nervous system. However, presence of the blood–brain barrier (BBB) strongly limits applicability of intravenous or oral paths for administration of drugs acting in the brain. Intranasal delivery is a promising, non-invasive strategy to bypass the BBB and deliver drugs directly to the brain. This review examines the nasal-to-brain delivery mechanisms, enhancement strategies, and therapeutic applications of drug delivery to the brain upon intranasal administration, with a focus on peptide delivery. It compares the anatomical differences in nasal cavity structure between humans and model animals used to study delivery efficacy and considers transport mechanisms, including intracellular (axonal) and extracellular (paracellular and transcellular) pathways. Peptide drugs approved for intranasal administration, such as insulin, exendin, and oxytocin as well as several peptides on the development stage are discussed in more details with insights of the influence of peptide sequence on the delivery efficiency. Finally, recent progress in various strategies to improve intranasal peptide delivery, including PEGylation, cell-penetrating peptides, and cyclodextrins are discussed.